2009
DOI: 10.14430/arctic198
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Recent Treeline Dynamics in Southwest Yukon from Aerial Photographs

Abstract: Small-scale vertical aerial photographs taken in 1947 and 1948 covering 200 km 2 of the Kluane Ranges, southwest Yukon, were compared with corresponding photographs taken in 1989 for the purpose of characterizing changes in the distribution and abundance of white spruce (Picea glauca (Moench) Voss) at the alpine treeline. Digital photogrammetry, including orthorectification and on-screen interpretation, was supplemented by stereoscopic inspection of the original prints. Qualitative assessment of change across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 31 publications
(28 reference statements)
2
37
1
4
Order By: Relevance
“…Los cambios en la tree line no sólo se evidencian a través del desplazamiento altitudinal en que aparecen los árboles, sino que también pueden detectarse a través del grado de recubrimiento boscoso de las zonas cercanas y del crecimiento interno del propio bosque (Danby and Hik, 2007). Así pues, durante el proceso de fotointerpretación también se ha tenido en cuenta este factor, determinando la densidad arbórea en cada una de las áreas delimitadas por una cuadrícula regular.…”
Section: Fotointerpretaciónunclassified
See 3 more Smart Citations
“…Los cambios en la tree line no sólo se evidencian a través del desplazamiento altitudinal en que aparecen los árboles, sino que también pueden detectarse a través del grado de recubrimiento boscoso de las zonas cercanas y del crecimiento interno del propio bosque (Danby and Hik, 2007). Así pues, durante el proceso de fotointerpretación también se ha tenido en cuenta este factor, determinando la densidad arbórea en cada una de las áreas delimitadas por una cuadrícula regular.…”
Section: Fotointerpretaciónunclassified
“…Aunque en este trabajo no se han abordado cuestiones relacionadas con la gestión del bosque y su explotación, esta constatación es importante ya que la densificación del bosque en sus zonas más cercanas a la tree line es uno de los indicadores (junto con las variaciones del límite altitudinal del bosque y el grado de desarrollo de los árboles) utilizados en estudios que relacionan estos signos con el cambio climático (Danby & Hik, 2007). En este sentido, la metodología aplicada parece adecuada para trabajos futuros que apunten en esta dirección.…”
Section: Conclusionesunclassified
See 2 more Smart Citations
“…Current findings indicate that treeline movement has not occurred uniformly across the northern hemisphere in recent decades, though evidence of a recession of the treeline has not been prevalent Harsch et al, 2009). Recent treeline advance has been observed in Quebec (Gamache & Payette, 2005;Caccianiga & Payette, 2006), northern Alaska (Suarez et al, 1999), the Kluane Range of Yukon (Danby & Hik, 2007), and the Polar Urals of Siberia 8 (Devi et al, 2008). Conversely, other studies have indicated a relatively stable treeline across Canada, with little to no advancement in recent decades (Szeicz & MacDonald, 1995b;Masek, 2001).…”
Section: Treeline and The Forest-tundra Ecotonementioning
confidence: 73%